Source-Network-Load-Storage Coordinated Control System Based on Distribution IOT Cloud Platform and Virtual Power Plant. Issue 1 (March 2021) - Han, T; Jiang, G D; Sun, B H; Feng, R Q; Wang, B W; Cao, L L
Abstract: In view of the distribution network operation problems caused by many distributed generations integration to distribution network, and the increasingly serious peak valley imbalance in grid, this paper proposes a coordinated control system of source-network-load-storage based on virtual power plant technology, which is designed and implemented in the actual project. The system uses cloud platform technology and multi-energy complementary technology to realize coordination and optimization control mechanism between sources, network and loads in regional distribution network. The system is based on the distribution Internet of things cloud master platform. Through the virtual power plant technology, resources such as cogeneration, photovoltaic, wind, distributed energy storage, electric vehicles, flexible loads are aggregated to achieve coordinated and unified control, realize the optimal operation of multi-energy complementary. It can accept the control of the dispatching center, and participate in the power transaction of demand response. Based on the application scenario, this paper explains how to use virtual power plant technology to participate in demand response power transaction, and describes the transaction rules and processes. The system is beneficial to the safety and reliability of the distribution network. It can implement reasonable configuration and consumption of distribution generations. It can control controllable loads such as electric vehicle charging pile to participate in peak regulation of power grid, and provide strong technical support for the realization of demand response.